2020
DOI: 10.1002/anie.201913865
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Iron–Nickel Nanoparticles for Magnetically Induced CO2Methanation in Continuous Flow

Abstract: Induction heating of magnetic nanoparticles (NPs) is a method to activate heterogeneous catalytic reactions. It requires nano‐objects displaying high heating power and excellent catalytic activity. Here, using a surface engineering approach, bimetallic NPs are used for magnetically induced CO2 methanation, acting both as heating agent and catalyst. The organometallic synthesis of Fe30Ni70 NPs displaying high heating powers at low magnetic field amplitudes is described. The NPs are active but only slightly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 43 publications
2
64
0
1
Order By: Relevance
“…FeNi3@Ni NPs were prepared following the procedure recently reported by De Masi et al and is described in the supplementary information. 48 These particles can be obtained by reduction of the organometallic precursors {Fe[N(SiMe3)2]2}2 and Ni[ i PrNC(CH3)N i Pr]2, under H2 in the presence of palmitic acid. As prepared, the particles possess a Fe-Ni core with a Fe-rich surface.…”
Section: Experimental Partmentioning
confidence: 99%
“…FeNi3@Ni NPs were prepared following the procedure recently reported by De Masi et al and is described in the supplementary information. 48 These particles can be obtained by reduction of the organometallic precursors {Fe[N(SiMe3)2]2}2 and Ni[ i PrNC(CH3)N i Pr]2, under H2 in the presence of palmitic acid. As prepared, the particles possess a Fe-Ni core with a Fe-rich surface.…”
Section: Experimental Partmentioning
confidence: 99%
“…18). 296 Fascinatingly, the Fe-Ni based bimetallic cluster also acted as a superior heating agent under a low magnetic field. Interestingly, bimetallic Au-Cu embedded Cu submicron arrays demonstrated the capability of ethanol formation through CO 2 reduction.…”
Section: Metal Nps As Active Sites For Co 2 Conversionmentioning
confidence: 99%
“…Magnetically induced catalysis is based on the heat generated by magnetic nanoparticles (NPs) when exposed to an alternating magnetic field . Recently, it has been demonstrated that this approach can be used to perform heterogeneous reactions at high temperature, such as CO 2 hydrogenation, using Fe 2.2 C NPs as heating agents and Ni or Ru NPs supported on SiRAlOx as catalysts, or by using bimetallic FeNi alloys as both heating agent and catalyst . However, one important limitation of these metallic heating agents is that they are prone to oxidation, so that they must be handled under inert atmosphere to preserve their heating capacities.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] Recently, it has been demonstrated that this approach can be used to perform heterogeneous reactions at high temperature, such as CO 2 hydrogenation, using Fe 2.2 C NPs as heating agents and Ni or Ru NPs supported on SiRAlOx as catalysts, [3][4][5] or by using bimetallic FeNi alloys as both heating agent and catalyst. [6] However, one important limitation of these metallic heating agents is that they are prone to oxidation, so that they must be handled under inert atmosphere to preserve their heating capacities. Additionally, these materials sinter under the harsh reaction conditions (above 320-400 8C), which diminishes their heating performance, consequently excluding their recyclability.…”
mentioning
confidence: 99%